2013
DOI: 10.1002/app.40234
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder‐based crosslinked self‐healing polyurethane/urea from polymeric methylene diphenyl diisocyanate

Abstract: Crosslinked self-healing polyurethane/urea based on a Diels-Alder reaction (C-PMPU-DA) was synthesized from a multiple-furan monomer and a commercial bismaleimide. The multiple-furan monomer (PMPU-furan) was obtained from a functionalized prepolymer (polymeric MDI: PBA-2000 5 2:1) by furfuryl amine. The structures of both the PMPU-furan and C-PMPU-DA were characterized by attenuated total reflectance (ATR)-Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry, thermogravimetric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 44 publications
0
51
0
1
Order By: Relevance
“…This effect was also observed by Kavitha and Singha [16][17][18][19]. Additional, other studies revealed that more polar environments of the maleimide/furan unit resulted in a slightly decreased rDA temperature [25][26][27][28]. Toncelli et al pointed out that at relatively low maleimide/furan ratio the RDA transitions become broader and shifts asymmetrically towards lower temperatures, while the crosslinking density drops significantly.…”
Section: A N U S C R I P Tmentioning
confidence: 49%
“…This effect was also observed by Kavitha and Singha [16][17][18][19]. Additional, other studies revealed that more polar environments of the maleimide/furan unit resulted in a slightly decreased rDA temperature [25][26][27][28]. Toncelli et al pointed out that at relatively low maleimide/furan ratio the RDA transitions become broader and shifts asymmetrically towards lower temperatures, while the crosslinking density drops significantly.…”
Section: A N U S C R I P Tmentioning
confidence: 49%
“…During the development of self-healing material much attention is often given to the understanding the mechanistic perspective of a given reaction as much as possible. Such studies are frequently accompanied by kinetic investigations of the reaction [11][12][13][14][15][16]. Benzoxazines, because of their unique characteristics, are recently gaining much attention in polymer synthesis and design.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the two series of networks, Ursache et al -eXPRESS Polymer Letters Vol.11, No.6 (2017) there can be noticed that the use of TF-2 instead of TF-1 in the synthesis of networks leads to a higher rDA temperature of networks which varies in the range of 138.90 and 141.64°C. The obtained values of the T rDA for the crosslinked networks were higher than the ones of similar networks from other studies [38,39]. The thermally reversible character of the compounds can be evidenced with DSC by applying multiple heating-cooling cycles to the sample.…”
Section: Dscmentioning
confidence: 60%